ТRENDS OF DEVELOPMENT OF THE TOURIST INDUSTRY OF THE LVIV REGION IN THE CONDITIONS OF A PANDEMIC - LUSHCHYK, MARIYA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article describes the current state of functioning of the tourist sector of Khmelnytsky region. In particular, the dynamics of changes in the number of tourists served by tourism entities, including: foreign tourists, citizens of Ukraine who traveled abroad, domestic tourists and excursionists were analyzed. The geography of arrival of foreign tourists to Ukraine is characterized, the features of transfer, residence, average stay and purpose of visit of foreign citizens are revealed, the distribution of tourists-citizens of Ukraine on the countries of their travel is analyzed.The specifics of excursion activity in the region are investigated. The information about the subjects of the tourist industry of the region is systematized. Courses of guides within the region are described. The activity of institutions of state regulation of tourism, tourist public organizations and associations, tourist information centers within the region is described.Monitoring of modern projects and initiatives in the field of tourism («Creation of innovative tourist infrastructure of Khmelnytsky region with tourist and logistics center in Khmelnytsky», «Ancient buildings speak», «Creation of tourist information center in the resort area of Sataniv Gorodok district Khmelnitsky region», «Creation of the tourist and recreational zone «Potocki Square» in the village of Antonina Krasyliv district of Khmelnytsky region «), which have a direct impact on the functioning of the tourism industry of Khmelnytsky region has been carried out.The main directions of tourism development in the region, namely: overcoming negative stereotypes about the city, promoting the region as an eco-friendly, safe and comfortable region, restoration and revitalization of historical and cultural monuments, active marketing of affordable event and gastronomic, art and shopping tourism, presentation of the tourist potential of the region at specialized tourist events, introduction of innovations in the tourist market (sensory tourist kiosks, programs «Living Museum»), types of diversification of accommodation facilities, etc., are listed.
Keywords: tourist industry; tourist flows; foreign tourists; domestic tourists; excursionists; tourist information centers